PENGATURAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN BADAN USAHA MILIK NEGARA (TJSL BUMN) PADA PT TIMAH TBK: Regulation of Social and Environmental Responsibility of State-Owned Enterprises (TJSL BUMN) in PT Timah Tbk - Keisyha Amanda Putri; Yunari, Sri Bakti (Faculty of Law, Universitas Trisakti, 2025)
Social and Environmental Responsibility (TJSL) in SOEs (BUMN) in Indonesia is a requirement as intended in Paragraph (1) Article 88 of Law Number 19 of 2003 concerning State-Owned Enterprises. This is no exception for PT Timah Tbk which has a business in the unitary segment of tin mining activities starting from exploration of mining areas, and mining activities to processing and marketing of Tin products. The rules regarding TJSL BUMN experience dynamic changes from time to time as evidenced by the Decree of the Minister of Finance No. 1232/KK.013/1989 to the newest regulation, namely Ministry of BUMN Regulation Number PER-1 /MBU/03/2023. Through normative-descriptive research methods, the author analyzes the TJSL regulations of BUMN which are further regulated through internal company regulations, especially by PT Timah Tbk. Through this research, it can be concluded that PT Timah Tbk has internal regulations regarding BUMN TJSL based on applicable regulations. However, there are still several obstacles to implementing them, such as existing company regulations which are still based on BUMN Ministerial Regulation Number PER-6 /MBU/09/2022 The recommendation given is that PT Timah Tbk company regulations need to be formed in implementing TJSL based on new regulations, namely BUMN Ministerial Regulation Number PER-1 /MBU/03/2023.